ANALISIS KECERDASAN EMOSIONAL DENGAN PROFIL PELAJAR PANCASILA PESERTA DIDIK KELAS V SEKOLAH DASAR GUGUS II KECAMATAN KAHU KABUPATEN BONE - A. Nurul Azizah Purnama Muhlis; Widya Karmila Sari Achmad; Hardianto Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of students’ emotional intelligence, the Profile of Pancasila Students in the dimensions of Global Diversity and Mutual Cooperation, and the relationship between emotional intelligence and these two dimensions among fifth-grade students of elementary schools in Cluster II, Kahu District, Bone Regency. This research employed a quantitative method with an ex post facto design. The population consisted of 146 students, with a sample of 107 students determined using the Slovin formula. Data were collected through questionnaires measuring emotional intelligence, the Global Diversity dimension, and the Mutual Cooperation dimension. Data analysis was conducted using descriptive and inferential statistics, including tests of normality, homogeneity, linearity, and t-test, with the assistance of IBM SPSS Statistics Version 25. The results showed that students’ emotional intelligence was in the good category, while the Global Diversity and Mutual Cooperation dimensions of the Pancasila Student Profile were in the moderate category. Furthermore, there were significant relationships between emotional intelligence and both dimensions. In conclusion, emotional intelligence plays an important role in shaping students’ character in accordance with the Pancasila Student Profile, particularly in appreciating diversity and collaborating with others. Therefore, strengthening emotional intelligence and integrating the values of the Pancasila Student Profile into the curriculum, school programs, and family support are highly recommended.